COMMON PHYSICAL PROBLEMS AMONG THE ELDERLY IN THE LIVINGSTONE DISTRICT IN ZAMBIA: OPPORTUNITIES FOR PHYSIOTHERAPISTS - Malambo, Passmore; Marais, Margaret (Journal of Community and Health Sciences, 2020)
Introduction: The study identified prevalent physical problems with regard to physiotherapy needs in elderly people in the Livingstone District in Zambia. Objectives: To identify the physiotherapy needs of common physical problems in the elderly. Methods: A cross-sectional study design, utilising a quantitative research method and a convenience sampling technique. Participants: A total of 200 elderly people from the age of 60 years Setting: Livingstone District in Zambia Intervention: A structured self-administered questionnaire was used to collect data. Results: The most common self-reported physical problems identified were musculoskeletal problems, physical inactivity, decreased ability to walk and the need for walking aids. Hypertension was a common cardiovascular disorder. Conclusion: Physiotherapists are ideally suited to alleviate the discomfort, activity limitation and participation restriction associated with ageing.